Comparasion between European elite senior and junior female table tennis players: Rally length and serve-receive game - Davide Luini Jason; Fuchs Michael; Đokic Zoran; Malagoli Lanzoni Ivan; Munivrana Goran (TIMS: Acta, 2021)
The aim of the study was to compare elite junior and senior women table tennis players, using three parameters of the table tennis: rally length, serve and receive analysis. Twenty-five junior and twenty-five elite senior matches were analysed (total: 263 sets and 4958 points) between players ranked in Top 25 in ETTU rankings in the last two years. All the athletes used an offensive style of play. The results of non-parametric Mann-Whitney U Test, showed a significantly higher rally length in senior compared to junior category (4.46 vs. 3.93). Moreover, the results of Pearson's Chi-square tests show an association between the age categories and selected parameters (laterality, technique and placement) for both serve and receive. Different behavior between the two categories was noted. The senior players used more the flip technique (22.2 % vs 14.7 %) and short push to return the services of the opponents (32.5 % vs 26.0 %). These results provide useful information to analyze junior players' behavior compared to the senior players in order to plan specific training sessions. It can be also useful to identify some parameters as predictors of the future success for junior players.